Expert Teaming – Bridging the Divide Between Party-Appointed and Tribunal Appointed Experts - Schmidt-Ahrendts, Nils (Victoria University of Wellington Law Review, 2012)
It appears to be a given in international arbitration that expert evidence is provided by party-appointed experts. This is despite the fact that one increasingly hears complaints that such evidence is of little value because it advocates too much in the interests of the party presenting it and tribunals often have to decide between diametrically opposite opinions and irreconcilable conclusions. While techniques such as "pre-hearing meetings" and "witness conferencing" seek to address these concerns, international arbitral practice has shown that these techniques are not always sufficient to combat the disadvantages of party-appointed experts. Fewer efforts have been made to remove the concerns expressed with regard to tribunal-appointed experts. This article describes a technique which seeks to combine the advantages of party-appointed and tribunal-appointed experts. The technique has been successfully applied in several International Criminal Court arbitration proceedings and has become known as "expert teaming" as well as the "Sachs Protocol".